Characterisation and Hypolipidaemic Effects of Tlayudas, Widely Consumed Tortillas, Containing Ganoderma lucidum Extracts on an In Vivo Model of Hypercholesterolaemia - Grace Preciado Iñiga; Daniel Martínez-Carrera; María E. Meneses; Miguel Sánchez; Adrián Argumedo; Myrna Bonilla; Ivan Castillo; Beatriz Petlacalco; Alfredo Morales; Nora Fernández; Wilfrido Martínez; Juan Antonio-Bautista; et al. (International Journal of Food Science)
Tlayudas, a variant of tortillas, are a highly consumed and low-cost traditional Mexican food, typical of the Oaxaca region. We developed new functional food products from tlayudas (T) containing standardised hydroalcoholic extracts (T + Gl-1 and T + Gl-2) of the medicinal mushroom Ganoderma lucidum (Gl) from Mexico. These products were characterised through physicochemical and sensory properties, analysis of bioactive compounds and hypolipidaemic capacity using an in vivo model (C57BL/6 mice) of hypercholesterolaemia. Tlayudas containing Gl extracts are more resistant (higher cutting force) and have better sensory attributes (appearance, colour, smell, flavour, texture and acceptability). Several nutritional components and functional properties improved significantly in comparison with the control; polyunsaturated fat increased 2.3% (T + Gl-1 and T + Gl-2), total polyphenols increased from 8.2% (T + Gl-1) to 14.2% (T + Gl-2), the antioxidant capacity by oxygen radical absorbance capacity (ORAC) from 7.3% (T + Gl-1) to 16.5% (T + Gl-2) and the content of β-glucans from 16.6% (T + Gl-1) to 100% (T + Gl-2). The heat treatment (ca. 400°C for 6.40 min) of the tlayudas cooking process did not lead to denaturing of G. lucidum compounds, remaining bioactive and stable in the food matrix. Tlayudas containing Gl extracts (T + Gl-1 and T + Gl-2) decreased main serum levels of cholesterol (–21.1% and –27.5%), triglycerides (–15.1% and –25.1%) and LDL-c (–55.4% and –62.7%) in C57BL/6 mice groups studied, as well as levels of glucose (–10.4% and –31.3%) and transaminases (ALT: –40.9% and –49.7%; AST: –36.1% and –34.5%), respectively, compared with the high-cholesterol (HC) diet. Tlayudas containing the Gl-2 extract decreased serum lipids and glucose levels further than the atorvastatin drug. These new functional food products with hypolipidaemic properties could be used to promote healthier diets for preventing cardiovascular and chronic degenerative diseases in target populations.